2021
DOI: 10.21203/rs.3.rs-448267/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigation of Effects of Silymarin in 5-Fluorouracil Hepatotoxicity and Nephrotoxicity in Mice

Abstract: Hepatotoxicity and nephrotoxicity are common side effects of 5-Fluorouracil (5-FU). The present study aimed to investigate the effects of Silymarin (SLY) on 5-FU induced hepatotoxicity and nephrotoxicity in mice. In our study, 10 mice in each group were randomly divided into four groups as the control group, 5-FU, SLY50+5-FU, and SLY100+5-FU group. SLY50+5-FU and SLY100+5-FU groups were administered at a dose of 50 and 100 mg/kg for seven days, respectively. 5-FU was administered at a dose of 400 mg/kg intrape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Contributing to antioxidant defense systems in different ways, silymarin inhibits free radicals directly and the enzymes that cause these radicals to form [ 24 ]. In a study, when they looked at the therapeutic effects of silymarin and naringin against methotrexate-induced nephrotoxicity, silymarin was administered at 50 mg/kg for seven days.…”
Section: Discussionmentioning
confidence: 99%
“…Contributing to antioxidant defense systems in different ways, silymarin inhibits free radicals directly and the enzymes that cause these radicals to form [ 24 ]. In a study, when they looked at the therapeutic effects of silymarin and naringin against methotrexate-induced nephrotoxicity, silymarin was administered at 50 mg/kg for seven days.…”
Section: Discussionmentioning
confidence: 99%
“…The liver is the major source of albumin synthesis. A decrease in serum albumin possibly suggests inflammation, chronic infections, kidney problems, and cirrhosis, among others [ 16 , 17 ]. The decreased albumin concentration in the patients suggests that some level of hepatocyte damage may occur following chemotherapy exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased albumin concentration in the patients suggests that some level of hepatocyte damage may occur following chemotherapy exposure. Normally, the lowering of albumin level indicates a liver disease [ 16 ]. This reduction could be attributed to changes in the free amino acid and protein metabolism and their synthesis in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…SIL can play a protective role in 5-FLU induced oxidative stress in liver and kidney tissues by eliminates 5-FLU toxicity. The study concluded that this kind of effect is due to the powerful antioxidant and anti-inflammatory properties of SIL [49].…”
Section: Silymarin and Chemotherapeutic Drugsmentioning
confidence: 92%